KONTEN SINETRON TELEVISI INDONESIA DI TINJAU DARI PERSPEKTIF ISLAM (Studi Kasus Sinetron Amanah Wali 6 RCTI) - Muhamad Tsaltsa Dinata; Dewi Anggrayni (Universitas Pahlawan Tuanku Tambusai, 2022)
The spectacle should be a guide for the wider community, that's how the media should be presented. Society must not only be presented by entertainment but have a bad impact on the character of the nation, the media has a great influence on how society models. So is it appropriate that the indecent scene be used as an example that becomes a daily entertainment for the people of Indonesia. This soap opera is very popular today as a means of conveying educational messages to the audience. In Indonesia, the duration of this soap opera reaches approximately 2 hours per episode. Of the four television stations that have soap opera programs, 26 soap operas are currently airing on television stations that are often watched by the Indonesian public. This soap opera is very popular today as a means of conveying educational messages to the audience. In Indonesia, the duration of this soap opera reaches approximately 2 hours per episode. Of the four television stations that have soap opera programs, 26 soap operas are currently airing on television stations that are often watched by the Indonesian public. One of the delivery of educational messages in the soap opera amanah wali 6 RCTI which has a religious background. The trustee's soap opera 6 tells the story of four market thugs who have been converted Therefore, the author chose this soap opera as the object of research. The purpose of this study is to determine the value of education in the Islamic perspective in the amanah wali 6 soap opera. The benefit of this research is to provide knowledge about semiotic analysis of educational messages in an Islamic perspective with Ferdinand De Saussure's theory in a soap opera and is expected to be a reference in analyzing soap operas using an Islamic perspective. The author uses a qualitative research method using Ferdinand De Saussure's semiotic analysis using signified components in the form of visuals and audio and signifiers related to the interpretation of signified. The results showed that in the amanah wali 6 episode 480 soap opera in 11 scenes formed 7 educational messages in the amanah wali 6 soap opera, namely; the privilege of dawn prayer, Allah is all-helping and all-giver of sustenance, don't hunt for guesswork, don't forget death, be sincere, don't neglect prayers, never eat from illicit money. Keywoard: soap operas, television, educational value